Sound Attenuation in Aspen Wood (Populus Tremula) Modified by Ultrasonic Method - Vjuginova, Alena A.; Bunakov, Anton; Teplyakova, Aleksandra V. (IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference, 2024)
In this paper sound attenuation in aspen wood (Populus tremula) modified by ultrasonic technology for improving of surface density and hardness was investigated. This technology is implemented by ultrasonic equipment of the pass-through type: the transported lumber or wood product, sawn timber with plane-parallel faces is exposed to high-intensity ultrasonic vibrations in combination with mechanical pressure, the result of this processing technology is modified wood surface layer with thickness about 1-2 mm, and the task of the present research is study the influence of the modified layer on sound attenuation of wood construction materials. Measurements of sound attenuation were realized by ultrasonic transmission method with dry acoustic contact. The results are presented in the form of dependences of sound attenuation on wood modification degree.